2001
DOI: 10.1177/112067210101100406
|View full text |Cite
|
Sign up to set email alerts
|

Retinal vein Occlusion and Factor V Leiden and Prothrombin 20210 G:A Mutations

Abstract: There was no significant association between retinal vein occlusion and the factor V Leiden mutation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 26 publications
(37 reference statements)
0
9
0
Order By: Relevance
“…However, no differences in the frequency of the Factor V G1691A polymorphism between RVO cases and controls were reported in studies of Turkish populations [ 22 , 32 , 36 ]. Janssen et al performed a meta-analysis of 12 studies [ 12 , 13 , 17 , 22 , 27 , 33 , 34 , 39 , 41 , 42 , 46 , 47 ] and found that the Factor V Leiden mutation (G/A+A/A) was associated with an increased risk of RVO [ 48 ]. Rehak et al performed a meta-analysis of 18 studies [ 13 , 14 , 17 , 19 , 22 , 29 , 31 , 34 , 37 , 40 42 , 47 , 49 53 ] and reported similar results [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, no differences in the frequency of the Factor V G1691A polymorphism between RVO cases and controls were reported in studies of Turkish populations [ 22 , 32 , 36 ]. Janssen et al performed a meta-analysis of 12 studies [ 12 , 13 , 17 , 22 , 27 , 33 , 34 , 39 , 41 , 42 , 46 , 47 ] and found that the Factor V Leiden mutation (G/A+A/A) was associated with an increased risk of RVO [ 48 ]. Rehak et al performed a meta-analysis of 18 studies [ 13 , 14 , 17 , 19 , 22 , 29 , 31 , 34 , 37 , 40 42 , 47 , 49 53 ] and reported similar results [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Janssen et al performed a meta-analysis of 12 studies [ 12 , 13 , 17 , 22 , 27 , 33 , 34 , 39 , 41 , 42 , 46 , 47 ] and found that the Factor V Leiden mutation (G/A+A/A) was associated with an increased risk of RVO [ 48 ]. Rehak et al performed a meta-analysis of 18 studies [ 13 , 14 , 17 , 19 , 22 , 29 , 31 , 34 , 37 , 40 42 , 47 , 49 53 ] and reported similar results [ 52 ]. Finally, Yioti et al performed a meta-analysis of 21 case-control studies [ 11 14 , 16 – 19 , 21 23 , 28 , 29 , 33 , 34 , 37 , 41 , 42 , 51 , 53 , 54 ] and demonstrated that the Factor V Leiden mutation was associated with an increased risk of RVO [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…32 , 40 43 Recent studies have found a high prevalence of FVL 21 , 24 , 26 28 and PTG mutations 58 , 59 in patients with OVO versus controls; however, some have not found the same. 16 , 29 , 30 – 32…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of thrombophilic mutations in patients presenting RVO in previous studies range from 0% to 17% for the factor V Leiden (16)(17)(18)(19)(20) , from 0% to 10% for PT 20210A (16,19,(21)(22)(23)(24) and from 3% to 19% for MTHFR 677TT (25)(26)(27)(28)(29)(30) . These differences may be related to the racial background, selection of the control group, and study design.…”
Section: Discussionmentioning
confidence: 99%
“…Studies investigating the presence of activated protein C resistance or factor V Leiden have suggested their potential role in RVO (16,25,29) . Recently, a study (31) also suggested that the presence of factor V Leiden increases the risk of neo-vascular complications in patients presenting central RVO.…”
Section: Discussionmentioning
confidence: 99%